Motives to use alcohol among adolescents according to their neighbourhood characteristics, gender, age, and drinking patterns - Simões, Celeste (2018)
The aim of this study is to understand if motives to drink are associated to certain patterns of drinking and specific socio-demographic drinkers’ characteristics. As part of the Portugal Health Behaviour in School-aged Children survey, developed with 5050 pupils (47.7% of boys), attending the 6th, 8th, and 10th grade levels and with a mean age of 13.98 years (SD = 1.85), the present study was carried out using the “Drinking Motive Questionnaire Revised Short Form” (Kuntsche & Kuntsche, 2009) in order to investigate the drinking motives among young people and its relationship with neighborhood characteristics, gender, age, and drinking patterns. Results showed that social motives are the most frequent, followed by enhancement, coping, and conformity motives. Statistically significant differences were found between gender and grade (a proxy for age), being essentially the boys who consume more socially and the boys of the 8th grade that reported to consume for enhancement motives, cope with negative emotions, or to affirm themselves within peers group. Differences between the place of residence and consumption patterns are also found, showing that pupils who live in a neighborhood marked by many night entertainment venues, violence and theft, along with its location in an isolated area, have a significantly higher average in the four motives. Considering the drinking pattern, drinking to cope or for conformity motives are more common during the week and during the day, while drinking for social motives is more frequent during the day. Implications of the results for health and educational public policies are discussed.